1999
DOI: 10.1161/01.str.30.5.1076
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Corticomedullary Contrast: An Early Cerebral Computed Tomography Sign Indicating Malignant Middle Cerebral Artery Infarction

Abstract: Background and Purpose-No neuroradiological markers have been characterized that support a timely decision for decompressive surgery in malignant middle cerebral artery (MCA) infarction (mMCAI). This case-control study was designed to analyze whether early cerebral CT (CCT) scanning provides reliable information for the prospective selection of stroke patients at risk of developing mMCAI. Methods-Thirty-one pairs (nϭ62) were formed with cases (mMCAI) and controls (acute but not malignant MCA infarction) closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 32 publications
3
47
0
3
Order By: Relevance
“…Of these, 18 patients died, and the only predictor of outcome was major early CT hypodensity. Haring and colleagues 33 also demonstrated that major hypodensity in the MCA territory predicted herniation but found that attenuation of contrast between the gray and white matter was the single best predictor of this outcome in a study of 62 patients with hemispheric infarctions. In the analysis of radiographic factors by Krieger and colleagues, 12 only CT involvement of Ͼ50% of the MCA territory was found to predict fatal brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 18 patients died, and the only predictor of outcome was major early CT hypodensity. Haring and colleagues 33 also demonstrated that major hypodensity in the MCA territory predicted herniation but found that attenuation of contrast between the gray and white matter was the single best predictor of this outcome in a study of 62 patients with hemispheric infarctions. In the analysis of radiographic factors by Krieger and colleagues, 12 only CT involvement of Ͼ50% of the MCA territory was found to predict fatal brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is discussed here because it does often overlap with END; it has devastating consequences; and identifying reliable predictors of MMI has great implications on further management, especially in the context of performing early decompressive surgery. 20 Early CT predictors of MMI are large hypodensity of the middle cerebral artery territory, 21-27 the hyperdense middle cerebral artery sign, 25,26,28 perfusion deficit Ͼ66% of the middle cerebral artery territory, 24,27 and brain swelling 23,26 ; however, only the first 2 remained significant on multivariate analysis. 21,22,25 On DSA, carotid T occlusion was found to be a better predictor of MMI than CT in patients undergoing intra-arterial therapy.…”
Section: Malignant MMImentioning
confidence: 99%
“…9 Haghighi et al also found 28% cases with severe headaches, 27% with agitation, 5% with seizures, 18% with eye gaze impairment. 10 It is also equally important to exclude hemorrhage in patients who are on anti-coagulants or the one who is considered for endarterectomy. If infarct is hemorrhagic, anti-coagulants are unsafe.…”
Section: Discussionmentioning
confidence: 99%